2022
DOI: 10.1177/1934578x221118213
|View full text |Cite
|
Sign up to set email alerts
|

Rutin Suppresses DMBA Carcinogenesis in the Breast Through Modulating IL-6/NF-κB, SRC1/HSP90 and ER-α

Abstract: Rutin dietary supplements may offer pharmacological benefits as anticancer and antiinflammatory properties. This study aimed to investigate the inhibitory and protective effect of rutin on signaling pathways of mammary gland carcinogenesis expermintally induced in female rats by 7,12-di-methyl benz (a) anthracene (DMBA). Results showed that rutin administration ameliorated DMBA toxicity and carcinogic effect on kidney and liver revealed by a significant decrease of urea and creatinine levels, and the activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Inflammation occurs in response to a chemical, physical or biological substance in the body (Ambriz-Pérez et al, 2016). TNF-α, IL-1β and MAPK14 are proinflammatory cytokines (Gur, Kandemir, et al, 2022;Temel et al, 2020) Previous studies have shown that RUT inhibits TNF-α and IL-1β levels in various tissues (Cihan et al, 2022;Kandemir, Caglayan, et al, 2020;Youssef et al, 2022). In the presented study, it was determined that there were significant increases in TNF-α, IL-1β and MAPK14 mRNA transcript levels in testicular tissue triggered by VALP application to rats.…”
Section: Discussionmentioning
confidence: 59%
“…Inflammation occurs in response to a chemical, physical or biological substance in the body (Ambriz-Pérez et al, 2016). TNF-α, IL-1β and MAPK14 are proinflammatory cytokines (Gur, Kandemir, et al, 2022;Temel et al, 2020) Previous studies have shown that RUT inhibits TNF-α and IL-1β levels in various tissues (Cihan et al, 2022;Kandemir, Caglayan, et al, 2020;Youssef et al, 2022). In the presented study, it was determined that there were significant increases in TNF-α, IL-1β and MAPK14 mRNA transcript levels in testicular tissue triggered by VALP application to rats.…”
Section: Discussionmentioning
confidence: 59%
“…The carcinogenicity of DMBA is known to be due to its mechanisms involved in DNA damage. Genes that play an essential role in cell growth and survival are damaged, causing mutations and an imbalance between cellular oxidants and antioxidants, which play an essential role in breast cancer development and progression [16].…”
Section: Resultsmentioning
confidence: 99%
“…Histopathological analysis in the control group that received the carcinogen DMBA showed a histological pattern of ductal carcinoma characterized by Available at www.veterinaryworld.org/Vol.17/March-2024/22.pdf malignancy criteria [28]. According to the American Society of Cancer, this histological change (ductal cancers) corresponds to the most frequent type of breast cancer in women [29].…”
Section: Discussionmentioning
confidence: 99%